2008
DOI: 10.1002/jcp.21573
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of AMP‐activated protein kinase and p38 mitogen‐activated protein kinase in 8‐Cl‐cAMP‐induced growth inhibition

Abstract: 8-Cl-cAMP (8-chloro-cyclic AMP), which induces differentiation, growth inhibition and apoptosis in various cancer cells, has been investigated as a putative anti-cancer drug. Although we reported that 8-Cl-cAMP induces growth inhibition via p38 mitogen-activated protein kinase (MAPK) and a metabolite of 8-Cl-cAMP, 8-Cl-adenosine mediates this process, the action mechanism of 8-Cl-cAMP is still uncertain. In this study, it was found that 8-Cl-cAMP-induced growth inhibition is mediated by AMP-activated protein k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 35 publications
5
32
1
Order By: Relevance
“…1B and C). As published earlier [8,9], 8-Cl-cAMP increased the phosphorylation of AMPK and p38 MAPK in these cells ( Fig. 1B and C).…”
Section: -Cl-camp Suppresses Shc1 Phosphorylation In Cancer Cellssupporting
confidence: 64%
See 1 more Smart Citation
“…1B and C). As published earlier [8,9], 8-Cl-cAMP increased the phosphorylation of AMPK and p38 MAPK in these cells ( Fig. 1B and C).…”
Section: -Cl-camp Suppresses Shc1 Phosphorylation In Cancer Cellssupporting
confidence: 64%
“…Previously, we showed that AMPK and p38 MAPK are essential factors for 8-Cl-cAMP-induced growth inhibition [8,9]. In this study, we revealed that p38 MAPK interacts with SHC1 (Fig.…”
Section: Discussionmentioning
confidence: 69%
“…29 In addition, compound C inhibited pro-apoptotic and anti-apoptotic actions of AMPK in various experimental settings 18,24,25,[30][31][32][33][34][35][36] and blocked AMPK-dependent autophagy in different types of normal and cancer cells. 25,[37][38][39] In the present study, contrary to expectations, we demonstrate for the first time the ability of compound C to induce autophagic response in different cancer cell lines.…”
mentioning
confidence: 99%
“…Thus, on the basis of the above results, p27 is functionally linked to the sensitivity of the RPMI-8226 cells to 8-Cl-cAMP-induced apoptosis. (15,21). Therefore, we evaluated the effect of 8-Cl-cAMP on p38 MAPK phosphorylation in the MM cells.…”
Section: -Cl-camp Induces Apoptosis In MM Cells Through a P27-dependmentioning
confidence: 99%
“…8-Cl-cAMP is a site-selective analog of cAMP. It has been reported that 8-Cl-cAMP shows a potent growth inhibitory effect and has reverse-transforming activity in cancer cells (15)(16)(17)(18). In the current study, we investigated the ability of 8-Cl-cAMP to induce apoptosis in two MM cell lines, RPMI-8226 and U266.…”
Section: Introductionmentioning
confidence: 97%